Peroxisomal Dysfunction in Neurological Diseases and Brain Aging - Uzor, Ndidi-Ese; McCullough, Louise D.; Tsvetkov, Andrey S. (Frontiers in Cellular Neuroscience, 2020)
Peroxisomes exist in most cells, where they participate in lipid metabolism, as well as scavenging the reactive oxygen species (ROS) that are produced as by-products of their metabolic functions. In certain tissues such as the liver and kidneys, peroxisomes have more specific roles, such as bile acid synthesis in the liver and steroidogenesis in the adrenal glands. In the brain, peroxisomes are critically involved in creating and maintaining the lipid content of cell membranes and the myelin sheath, highlighting their importance in the central nervous system (CNS). This review summarizes the peroxisomal lifecycle, then examines the literature that establishes a link between peroxisomal dysfunction, cellular aging, and age-related disorders that affect the CNS. This review also discusses the gap of knowledge in research on peroxisomes in the CNS